Komunikasi Pedagogis Pendidikan Tinggi Kehutanan dalam Perspektif Kritis - Mutiono Mutiono; Sarwititi Sarwoprasodjo; Sudarsono Soedomo; Heri Budianto (Institut Pertanian Bogor, 2018)
The emergence of various forest resources problem in Indonesia, pragmatically could not be launched from the processes that occured in higher education. As a manifestation of development communication events, pedagogical communication that occurs in forestry education was important to be observed. This paper aims to explain the facts that occured in the teaching and learning process at the selected Faculty of Forestry, including to explain epistemology that form those facts. The research paradigm is a critical paradigm in qualitative research. Samples were taken purposively by conducting classroom observations, in-depth interviews with students and lecturer, desk study and conducting Focus Group Discussion. The results of this research show that there are facts which lead to the ineffectiveness of pedagogical communication. There are at least 8 issues that became the impetus for the occurrence of such ineffectiveness. The situation has made the message construction thus was not carried but only administrative issues answered in ongoing pedagogical communication. It makes a silent culture increasingly wide spread and inquiries that build students awareness of being not able to grow.